HSP27 is a partner of JAK2-STAT5 and a potential therapeutic target in myelofibrosis - Margaux Sevin (Nature Portfolio, 2018)
Myelofibrosis is a chronic degenerative disorder characterized by progressive bone marrow fibrosis. Here, the authors show that the chaperone HSP27 contributes to myelofibrosis via regulation of the JAK2/STAT5 pathway, and that antisense oligonucleotides targeting HSP27 are effective in two mouse models of the disease